2019
DOI: 10.3390/nu11112736
|View full text |Cite
|
Sign up to set email alerts
|

Rice Bran Derived Bioactive Compounds Modulate Risk Factors of Cardiovascular Disease and Type 2 Diabetes Mellitus: An Updated Review

Abstract: Cardiovascular disease (CVD) and type 2 diabetes mellitus (T2DM) are two chronic diseases that have claimed more lives globally than any other disease. Dietary supplementation of functional foods containing bioactive compounds is recognised to result in improvements in free-radical-mediated oxidative stress. Emerging evidence indicates that bioactive compounds derived from rice bran (RB) have therapeutic potential against cellular oxidative stress. This review aims to describe the mechanistic pathways behind C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 81 publications
2
15
0
5
Order By: Relevance
“…Moreover, we found that the FRB might be more effective in lowering ALDH levels at a concentration of 15% compared with the FRS. These results are in agreement with previous studies [64,65,67,70,79,[95][96][97].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Moreover, we found that the FRB might be more effective in lowering ALDH levels at a concentration of 15% compared with the FRS. These results are in agreement with previous studies [64,65,67,70,79,[95][96][97].…”
Section: Discussionsupporting
confidence: 94%
“…Our results indicate that the FRB might be more effective in lowering serum levels of AST, ALT and ALP at a concentration of 15% and those of LDH at a concentration of 30% compared with the FRS. This is in agreement with previously published studies showing that the FRB had a positive effect on serum levels of hepatic enzymes [30,31,[64][65][66][67][68][69][70][71][72][73].…”
Section: Discussionsupporting
confidence: 93%
“…Oxidative stress is generated due to an imbalance between the endogenous antioxidant systems in our body and free radicals such as reactive oxygen species [ 1 ]. This consequently results in chronic inflammation leading to cardiovascular complications [ 2 ]. The key role of macrophages in the innate immune system is to engulf foreign agents, eliminate apoptotic cells and resolve inflammation via inflammatory cytokines and other mediators [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, RB is known to be abundant in macronutrients and bioactive compounds such as p -coumaric acid, ferulic acid, and caffeic acid [ 20 ]. Although studies have demonstrated that RB phenolic compounds have the potential to exhibit antioxidant and/or anti-inflammatory properties [ 2 ], their impact on specific pathways of inflammation in an oxidative stress-induced/inflammatory environment has not been studied. The current study aimed to determine the antioxidant and anti-inflammatory effect of RB phenolic extracts on RAW264.7 mouse macrophage cells stimulated with hydrogen peroxide (H 2 O 2 ) and lipopolysaccharide (LPS).…”
Section: Introductionmentioning
confidence: 99%
“…Rice bran (RB), a by-product of the rice milling process, is usually discarded or used as animal feed [ 18 ]. However, the bran layer is composed of several bioactive phytochemicals, including polyphenols and phenolic acids [ 19 ]. Although RB phenolic extracts are believed to target metabolic pathways associated with T2DM, the mechanisms behind its effect on gene expression under normal and diabetic conditions have not been investigated.…”
Section: Introductionmentioning
confidence: 99%